2017
DOI: 10.1016/j.bbagen.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

2102Ep embryonal carcinoma cells have compromised respiration and shifted bioenergetic profile distinct from H9 human embryonic stem cells

Abstract: Recent studies have shown that cellular bioenergetics may be involved in stem cell differentiation. Considering that during cancerogenesis cells acquire numerous properties of stem cells, it is possible to assume that the energy metabolism in tumorigenic cells might be differently regulated. The aim of this study was to compare the mitochondrial bioenergetic profile of normal pluripotent human embryonic stem cells (hESC) and relatively nullipotent embryonal carcinoma cells (2102Ep cell line). We examined three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
(81 reference statements)
1
5
0
Order By: Relevance
“…AK2 and CKmit provide nucleotide exchange and metabolic signaling capacity, allowing mitochondria to export ATP and reception of cytosolic feedback signals such as ADP, AMP, and creatine (22,23,37). Phosphotransfer enzymes CK and AK have been implicated in cancer cell proliferation (35,36). In general, CK is involved in cancerous transformation, as CKB (brain-type CK) is upregulated in a variety of cancers to support growing energy needs (38).…”
Section: Adenylate Kinase 2 and Mitochondrial Creatine Kinase Interplmentioning
confidence: 99%
See 3 more Smart Citations
“…AK2 and CKmit provide nucleotide exchange and metabolic signaling capacity, allowing mitochondria to export ATP and reception of cytosolic feedback signals such as ADP, AMP, and creatine (22,23,37). Phosphotransfer enzymes CK and AK have been implicated in cancer cell proliferation (35,36). In general, CK is involved in cancerous transformation, as CKB (brain-type CK) is upregulated in a variety of cancers to support growing energy needs (38).…”
Section: Adenylate Kinase 2 and Mitochondrial Creatine Kinase Interplmentioning
confidence: 99%
“…However, in other cancer types, the downregulation of CKB and rewiring of metabolism may play an important role in colon cancer progression (40). Moreover, several studies have demonstrated that in colorectal cancer (41), breast cancer (42), neuroblastoma (35), prostate cancer (43), and sarcoma (36,44), the CKmit was downregulated. The reduction of CKmit in cancer cells was associated with the upregulation of adenylate kinase AK2 isoform in intermembrane space (36,41,42,45,46) (see Table 1).…”
Section: Adenylate Kinase 2 and Mitochondrial Creatine Kinase Interplmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that malignant cells' growth is favored by fermentative glycosis by so-called "Warburg effect", but there are clear evidence that oxidative phosphorylation could be used, to some extent by some tumors to derived their energy [68,69]. During cancerogensis energetic metabolism is differently regulated, total AK activity being almost three times higher in nullipotent embryonal carcinoma cells compared to normal pluripotent human embryonic stem cells [70]. More, there are evidence of production of ATP by mitochondrial oxidative phosphorylation in neuroblastoma cells, two enzymes being involved in this process-AK2 and hexokinase-2 [71].…”
Section: Adenylate Kinases and Cancermentioning
confidence: 99%